Metodika práce s třídním kolektivem v inkluzivní třídě se zaměřením na žáky s tělesným postižením Metodická příručka - Opatřilová, Dagmar (Masaryk University Press, 2020)
Title in English: Methodological publication of work with inclusive classroom with the focus on pupils with physical disability: Methodical Manual Publication is one of the outputs of the project Quality Inclusive Education of Pupils with Special Education Needs at elementary and secondary school. This text focuses on teaching pupils with physical disabilities in an inclusive classroom. The text is divided into three chapters, the first one defines theoretical background. Described is physical disability with an emphasis on cerebral palsy together with the specifics of the target group of pupils. Part of the chapter also defines special pedagogical diagnostics. The second chapter focuses on the education of pupil with cerebral palsy in inclusive school. In the third chapter are presented results of the research part of the project with special education needs - with physical disabilities with the focus on cerebral palsy.